1999
DOI: 10.3354/meps181237
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the nematode communities on the southeastern Weddell Sea shelf and slope (Antarctica)

Abstract: Nothing is known about the structure of free-living manne nematode coinmunities in the high Antarctic. Our attempt at surveying this n~unerically most abundant meiobenthic taxon along the continental shelf and slope (200 to 2000 m) furmshed information on generic, trophic and age composition in 2 regions in the Weddell Sea (Kapp Norvegia, 6 stations, 71-72"S, 12-13" W; Halley Bay, 11 stations, 74-75"S, 25-29" W). A total of 7300 nematode identifications to generic level were analyzed by means of a variety of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 32 publications
3
60
0
2
Order By: Relevance
“…For example, compilation of the published data did not reveal any prominent latitudinal gradients for shallow water free-living marine nematodes in the southern hemisphere, whereas the samples collected specifically along the coast of Chile between 18 and 42°S showed that sandy beach nematode fauna follows the classic latitudinal gradient (Boucher 1990, Lee & Riveros 2011. The wider inter-regional comparisons, however, did not show obvious latitudinal trends in nematode α diversity, in contrast to macrofauna (Vanhove et al 1999, Mokievsky & Azovsky 2002, Muthumbi et al 2004). Harpacticoids, aside from nematodes, are ubiquitous and often the most abundant component of marine meiofauna (Giere 2009).…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…For example, compilation of the published data did not reveal any prominent latitudinal gradients for shallow water free-living marine nematodes in the southern hemisphere, whereas the samples collected specifically along the coast of Chile between 18 and 42°S showed that sandy beach nematode fauna follows the classic latitudinal gradient (Boucher 1990, Lee & Riveros 2011. The wider inter-regional comparisons, however, did not show obvious latitudinal trends in nematode α diversity, in contrast to macrofauna (Vanhove et al 1999, Mokievsky & Azovsky 2002, Muthumbi et al 2004). Harpacticoids, aside from nematodes, are ubiquitous and often the most abundant component of marine meiofauna (Giere 2009).…”
mentioning
confidence: 98%
“…Several inter-regional comparisons of nematode α diversity, using various diversity indices, found no obvious latitudinal trends, in contrast to macrofauna (Vanhove et al 1999, Mo kievsky & Azovsky 2002, Muthumbi et al 2004. Changes in deep-sea nematode assemblages along bathymetrical gradients prevail over latitudinal gradients and references therein, Fonseca et al 2010).…”
Section: Relative Role Of Diversity Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hasemann and Soltwedel (2011) inferred that factors that influence the nematode community have different effects in different areas. Vanhove et al (1999) underlined that the spatial variability of the meiofauna and the different aggregations are related to different groups of factors (i.e. physical, chemical and biological) that can act together on meiobenthic communities.…”
Section: Different Benthic Size Classes In Relation To the Environmenmentioning
confidence: 99%